Efficiency, Technological Shift And Human Capital In The K-Economies Of Asean Five Plus Three - Wong, Mei Foong (2007)

(untitled)
Develop towards a knowledge-based economy is extremely important for the ASEAN five plus three countries, since the countries face challenges at the global fronts and technological changes; the rules of competition have changed. A country’s competitive advantage is no longer dependent solely on factors such as labor, land and natural resources, but on its potential to produce, acquire, utilize and disseminate knowledge. Thus, this is essentially a shift from economic development based on resources to development based on knowledge where human capital (consequently education) emerges as crucial public policy themes for creating wealth and increasing the quality of life. This thesis attempts to determine the level of knowledge-based development in Malaysia in terms of efficiency, technical change and human capital. This development is then compared with the other ASEAN five plus three countries,which includes four members of the Association of Southeast Asian Nations (ASEAN) namely Indonesia, the Philippines, Singapore, and Thailand and the three Northeast Asian states, namely China, Japan and South Korea. In particular, the objectives of this study are to (1) determine the contribution of knowledge-based human capital to economic growth in the ASEAN five plus three countries, (2) identify the determinants of knowledge-based human capital in Malaysia and the selected ASEAN five plus three countries, (3) determine the efficiency of Malaysian in generating the knowledge-based outputs, as compared to other ASEAN five plus three countries, and (4) investigate whether there is any long-run convergence in the development of knowledge-based human capital among Malaysia and the ASEAN five plus three countries. The empirical findings of the economic growth model using a panel cointegration framework and Fully Modified Ordinary Least Square (FMOLS) show that the human capital significantly influenced the economic growth in the ASEAN five plus three countries. Furthermore, the empirical results of the human capital analyses also indicate significant economic and demographic variables including the Gross Domestic Product (GDP) and fertility rate. However, the time series cointegration test did not detect a significant long-run convergence in the development of human capital among Malaysia and the ASEAN five plus three countries.The empirical findings of the Stochastic Frontier Analysis (SFA) indicate that Malaysia, Korea, Singapore, Japan and China appear to be the most efficient countries in generating the knowledge-based outputs, followed by Thailand though Indonesia and Philippines appear to be the least efficient countries. In regard to the issue of catch-up and convergence, the results show that Malaysia and Korea are catching up with the developed country such as Japan while other ASEAN five plus three countries are failed to catch-up with developed countries over the period. Last but not least, all the ASEAN five plus three countries have enjoyed from technical progress and achieved positive total factor productivity (TFP) growth rates over the 1992-2005 period.